Reclassification of Alcaligenes latus strains IAM 12599T and IAM 12664 and Pseudomonas saccharophila as Azohydromonas lata gen. nov., comb. nov., Azohydromonas australica sp. nov. and Pelomonas saccharophila gen. nov., comb. nov., respectively - Cheng‐Hui Xie; Akira Yokota (2005)
The aim of this study was to clarify the taxonomic position of the nitrogen-fixing and hydrogen-oxidizing bacteria Alcaligenes latus strains IAM 12599T, IAM 12664 and IAM 12665 and Pseudomonas saccharophila IAM 14368T. It was found that the type strain of Alcaligenes latus, IAM 12599T, showed 99 x 9 and 96 x 1 % 16S rRNA gene sequence similarity to strains IAM 12665 and IAM 12664, respectively. A comparison using DNA-DNA hybridization suggested that strains IAM 12599T and IAM 12665 belong to a single species (89 x 7 %) and that strain IAM 12664 (35 x 1 %) forms a separate species. The phenotypic characteristics also support the conclusion that these bacteria should be identified as two species of a new genus: Azohydromonas lata gen. nov., comb. nov. (type strain IAM 12599T=DSM 1122T=LMG 3321T=ATCC 29712T; reference strain IAM 12665=DSM 1123=LMG 3325=ATCC 29714) and Azohydromonas australica sp. nov. (type strain IAM 12664T=DSM 1124T=LMG 3324T=ATCC 29713T). Pseudomonas saccharophila IAM 14368T was found to be closely related to the phototrophic bacterium Roseateles depolymerans, with 96 x 8 % 16S rRNA gene sequence similarity, but the two bacteria are quite different with respect to their metabolism and some significant phenotypic characteristics, suggesting that they cannot be included in a single genus. Further studies on their nifH gene sequences, G+C content of the DNA and cellular fatty acid composition confirm that Pseudomonas saccharophila should be reclassified: the name Pelomonas saccharophila gen. nov., comb. nov. is proposed, with the type strain IAM 14368T (=LMG 2256T=ATCC 15946T).